Granulifera pulla gen. et sp. n. (Gastropoda, Pectinibranchia, Trochidae) из среднего миоцена Западной Украины - Анистратенко, О.Ю. (Вестник зоологии, 2000)
Из баденского яруса (cредний миоцен) Западной Украины описаны новый род и вид гастропод Granulifera pulla gen. et sp. n. из семейства Trochidae. Granulifera pulla – new genus and species of Gastropoda (Pectinibranchia, Trochidae) from Badenian (Middle Miîcene) of the Western Ukraine were described.